2002
DOI: 10.1248/cpb.50.869
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethanoid and Iridoid Glycosides from Veronica persica.

Abstract: In the flora of Turkey, the genus Veronica L. (Scrophulariaceae) is represented by 79 species, 26 of which are endemic.1) Some Veronica species are used as folk medicines in Turkey and in several other countries. [2][3][4][5] The genus Veronica is known to contain mainly iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid and flavonoid glycosides. [6][7][8][9][10] In previous studies, iridoid glucosides, phenylethanoid glycosides and alkaloids have been reported fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…cuneifolia and V. cymbalaria hemoptysis, laryngopharyngitis, hernia, cough, and respiratory diseases, and are also used as an expectorant and antiscorbutic (Tomassini et al, 1995;Su et al, 1999;Grahamet et al, 2000). Earlier investigations performed on Veronica species resulted in the isolation mainly of iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid, and flavonoid glycosides (Chari et al, 1981;Taskova et al, 1998;Harput et al, 2002aHarput et al, , 2002bSaracoglu et al, 2002;Jensen et al, 2005). In this study, Veronica cuneifolia subsp.…”
Section: Research Articlementioning
confidence: 82%
See 1 more Smart Citation
“…cuneifolia and V. cymbalaria hemoptysis, laryngopharyngitis, hernia, cough, and respiratory diseases, and are also used as an expectorant and antiscorbutic (Tomassini et al, 1995;Su et al, 1999;Grahamet et al, 2000). Earlier investigations performed on Veronica species resulted in the isolation mainly of iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid, and flavonoid glycosides (Chari et al, 1981;Taskova et al, 1998;Harput et al, 2002aHarput et al, , 2002bSaracoglu et al, 2002;Jensen et al, 2005). In this study, Veronica cuneifolia subsp.…”
Section: Research Articlementioning
confidence: 82%
“…As a consequence of these results, the genus Veronica has been transferred to the Plantaginaceae Olmstead, 2005). Recently, it has been shown that the iridoid glucosides aucubin, catalpol, and 6-O-catalpol esters are characteristic for this genus and chemotaxonomic research concerning iridoid content of the genus have great importance for the reclassification of the close genera (Harput et al, 2002a(Harput et al, , 2002bTaskova et al, 2004;Jensen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The results in this study supported this relationship, since the effects of 4-10 were not significant. The strong DPPH radical scavenging effects of 11 [34][35][36][37], 14 [34,37], 19 [38], and 20 [38] were previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Peak 7 corresponds to the majority (14.9 mg/g extract) phenolic compound in V. urticifolia extract. In fact, acteoside is a phenylethanoid glycoside, a group of phenolic compounds that is widely distributed in plants and was previously reported in Veronica species (Harput et al, 2002b;Johansen et al, 2007;Crişan et al, 2007), being inclusively considered as an important chemotaxonomic marker. The detected amounts of acteoside highlight V. urticifolia as a potential natural source of this bioactive compound, already reported as having antimicrobial (Avila et al, 1999), antigenotoxic (Zaabat et al, 2011) and antitumor (Ohno et al, 2002) properties.…”
Section: Hydroxycinnamoyl Derivativesmentioning
confidence: 99%